The impact of the dark web on internet governance and cyber security - Chertoff, Michael B. (Paper series, 2015)
The term deep Web is used to denote a class of content on the Internet that, for various technical reasons, is not indexed by search engines. The dark Web is a part of the deep Web that has been intentionally hidden and is inaccessible through standard Web browsers. A relatively known source for content that resides on the dark Web is found in the Tor network. Tor, and other similar networks, enables users to traverse the Web in near-complete anonymity by encrypting data packets and sending them through several network nodes, called onion routers.